HISTORIA, CIUDAD Y FILOSOFÍA LATINOAMERICANA EN JOSÉ LUIS ROMERO - Fielbaum S, Alejandro (2012)
After exposing the necessity of thinking philosophical development in the context of the urban space where its discourses appear and circulate, we expose the link that Romero draws between philosophy and city. The relation is thought in a wekear sense in Latin America than in the European case. That might be considered because Romero finds a rejection in latin American philosophy to think itself historically, in that refers to the city as its condition of possibility, what puts it in close to a dangerous populism that cannot think the modern urban culture in Latin America.